Molecular mechanisms of suberoylanilide hydroxamic acid in the inhibition of TGF‐β1‐mediated canine corneal fibrosis. (12th November 2015) - Gronkiewicz, Kristina M.; Giuliano, Elizabeth A.; Sharma, Ajay; Mohan, Rajiv R.
Abstract: Objective: To investigate molecular mechanisms mediating anti‐fibrotic effect of SAHA in the canine cornea using an in vitro model. We hypothesized that SAHA attenuates corneal fibrosis by modulating Smad‐dependent and, to a lesser extent, Smad‐independent signaling pathways activated by TGF‐β1, as well as matrix metalloproteinase (MMP) activity. Methods: Cultured canine corneal fibroblasts (CCF) were incubated in the presence/absence of TGF‐β1 (5 ng/mL) and SAHA (2.5 μm ) for 24 h. Western blot analysis was used to quantify non‐phosphorylated and phosphorylated isoforms of Smad2/3, p38 MAP kinase (MAPK), ERK1/2, and JNK1. Real‐time PCR and zymography were utilized to quantify MMP1, MMP2, MMP8, and MMP9 mRNA expressions and MMP2 and MMP9 protein activities, respectively. Results: TGF‐β1 treatment caused a significant increase in phospho‐Smad2/3 and phospho‐p38 MAPK. SAHA treatment reduced TGF‐β1‐induced phosphorylation of Smad2/3 but not of p38 MAPK. TGF‐β1 did not modulate the phosphorylation of ERK1/2 or JNK1. SAHA caused a significant reduction in phospho‐ERK1/2 expression regardless of concurrent TGF‐β1 treatment. Neither SAHA alone nor in combination with TGF‐β1 altered phospho‐JNK1 expression. TGF‐β1 significantly increased MMP1 and MMP9 mRNA expressions but did not alter MMP2 mRNA. SAHA treatment attenuated TGF‐β1‐induced MMP9 mRNA expression while significantly enhancing TGF‐β1‐induced MMP1 mRNA expression. Zymography detected reduced expression of MMP2 and MMP9 proteins in untreated control CCF. TGF‐β1 treatment did not alter their expression, but SAHA treatment +/−TGF‐β1 significantly increased MMP2 and MMP9 protein expressions. Conclusions: The corneal anti‐fibrotic effects of SAHA involve multiple mechanisms including modulation of canonical and non‐canonical components of TGF‐β1 intracellular signaling and MMP activity.